Effect of polyester fiber reinforcement on the mechanical properties of interim fixed partial dentures - N. Gopichander; K.V. Halini Kumarai; M. Vasanthakumar (Elsevier, 2015)
Background: Different reinforcements currently available for interim fixed partial denture (FPD) materials do not provide the ideal strength for long-term use. Therefore, the aim of this investigation was to develop a more ideal provisional material for long-term use with better mechanical properties. This study evaluated the effectiveness of polyester fiber reinforcement on different interim FPD materials. Methods: Thirty resin-bonded FPDs were constructed from three provisional interim FPD materials. Specimens were tested with a universal testing machine (UTM). The modulus of elasticity and flexural strength were recorded in MPa. The compressive strength and degree of deflection were calculated from the obtained values, and a two-way analysis of variance (ANOVA) was used to determine the significance. Results: The polyester fiber reinforcement increased the mechanical properties. The modulus of elasticity for heat-polymerized polymethyl methacrylate (PMMA) was 624 MPa, compared to 700.2 MPa for the reinforced heat-cured sample. The flexural strengths of the bis-acrylic and cold-polymerized reinforced samples increased significantly to 2807 MPa and 979.86 MPa, respectively, compared to the nonreinforced samples. The mean compressive strength of the reinforced cold-polymerized PMMA samples was 439.17 MPa; and for the reinforced heat-polymerized PMMA samples, it was 1117.41 MPa. The degree of deflection was significantly greater (P < 0.05) in the reinforced bis-acrylic sample (5.03 MPa), compared with the nonreinforced bis-acrylic sample (2.95 MPa). Conclusion: Within the limitations of this study, polyester fiber reinforcements improved the mechanical properties of heat-polymerized PMMA, cold-polymerized PMMA, and bis-acrylic provisional FPD materials. Keywords: Provisional FPD, Interim FPD, Polyester fiber reinforcement, Temporary FPD reinforcement